2002
DOI: 10.1021/nl015690z
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Selective Placement of Carbon Nanotubes on Pre-Patterned Electrodes

Abstract: Practical utilization of carbon nanotubes (CNTs) in nanoscale devices requires their directed placement on a substrate. Controlled placement has been achieved by a combination of the highly selective adsorption of single walled CNTs (SWNTs) onto open regions of amino-functionalized SiO 2 in a polymeric resist, followed by liftoff. Careful selection of the surfactant used to suspend the SWNTs as well as other processing parameters allow controlled placement in high yield. This technique may provide a path for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 7 publications
1
60
0
1
Order By: Relevance
“…As a result, considerable research focuses on developing techniques for depositing and patterning SWNTs from solution, as individuals or aggregates, with well-controlled coverage and alignment. Langmuir-Blodgett techniques [1][2][3][4] and various schemes of deposition from solution [5][6][7][8][9][10][11][12][13][14][15] have been studied extensively. Although these methods exhibit attractive features, they each have some combination of disadvantages, such as low deposition rate, inability to control tube alignment and/or to deposit over large areas, required chemical modification of the SWNTs or substrates, or the need for organic solvents that are incompatible with plastic device components (organic electrodes, semiconductors, or substrates).…”
mentioning
confidence: 99%
“…As a result, considerable research focuses on developing techniques for depositing and patterning SWNTs from solution, as individuals or aggregates, with well-controlled coverage and alignment. Langmuir-Blodgett techniques [1][2][3][4] and various schemes of deposition from solution [5][6][7][8][9][10][11][12][13][14][15] have been studied extensively. Although these methods exhibit attractive features, they each have some combination of disadvantages, such as low deposition rate, inability to control tube alignment and/or to deposit over large areas, required chemical modification of the SWNTs or substrates, or the need for organic solvents that are incompatible with plastic device components (organic electrodes, semiconductors, or substrates).…”
mentioning
confidence: 99%
“…[25][26][27] The affinity of semiconductor single-walled carbon nanotubes (SWCNT) towards basic nitrogen atoms is well-known. [28][29][30] As reported by Rouse,31 poly(4-vinylpyridine) (P4VP) performs well the role of bridge between CNT and solvent and hence is able to disperse them in alcoholic medium. P4VP was used by Vos and co-workers 32 to obtain stable suspensions of SWCNT or multi-walled carbon nanotube (MWCNT) with P4VP-based metallopolymers containing [M(bpy) 2 Cl]Cl, where M is Ru 2+ or Os 2+ and bpy is 2,2'-bipyridine.…”
Section: Introductionmentioning
confidence: 75%
“…[28][29][30] In order to check which interaction is dominant in P4VP/MWCNT pair, nuclear magnetic resonance experiments were conducted to investigate the effect of the presence of MWCNT on the chemical shifts of hydrogens and nitrogens of the polymer. shielded showing that, in the average, nitrogen does not donate electronic density to MWCNT walls and therefore charge-transfer interactions could be of minor importance.…”
Section: Resultsmentioning
confidence: 99%
“…This technique can be useful for positioning nanotube but has very poor directional control as the nanotubes often loop around the patterns. Several applications of this method to position nanotubes in between pairs of electrodes have been reported and only limited rate of reliable electrical contact of the device can be assured [10]. Huang et al reported on fluidic manipulation, utilizing flow assembly on a functionalized substrate.…”
Section: Introductionmentioning
confidence: 99%